Biaxial structured illumination microscopy with high measurement accuracy based on product processing. (September 2022) - Xie, Zhongye; Tang, Yan; He, Yu; Sun, Jinghua; Li, Jiaming; Luo, Zhichao
Highlights: In this paper, a BPSIM method with enhanced measurement accuracy is proposed. Two CCDs, one located in the focal plane and the other placed before or after the focal plane, are used to detect signals. By conducting a multiplication operation on these two signals, we obtain a product CDR, whose FWHM is smaller than CDR. Since the FWHM of PCDR is smaller than that of conventional CDR, an enhanced measurement accuracy can be achieved. The proposed BPSIM can find potential applications in precision measurement. Abstract: Structured illumination microscopy (SIM) has been established for non-fluorescent three-dimensional (3D) measurement with nanometer resolution. In SIM, a narrower full width at half maximum (FWHM) of contrast depth response (CDR) curve indicates a higher measurement resolution and accuracy. In this paper, we propose a biaxial structured illumination microscopy based on product processing (BPSIM) to achieve a high resolution and accurate reconstruction. In this method, two CCDs placed in biaxial optical paths are utilized to capture signals. After that, through conducting a multiplication operation on these two signals, a product CDR (PCDR) with narrow FWHM is achieved. Further, the peak position of PCDR for each pixel is extracted to realize 3D measurement. Owing to narrow FWHM of PCDR, an enhanced measurement accuracy and resolution can be obtained. The measurement error of step sample achieved by SIM and BPSIM is 14.5 nm and 8.7 nm respectively, justifying the proposed method can realize an improved accuracy. The simulations are also performed to demonstrate the feasibility of proposed method, indicating the potential to be applied in high precision measurement.